Computational study of electronic structure, thermodynamics and kinetics of hydrogen desorption from Al- and Si-doped alpha-, gamma-, and beta-MgH2 - Kelkar, Tuhina; Pal, Sourav (Journal of Materials Chemistry, 2009)
First principles calculations of pure and Al-and Si-doped alpha-, gamma-, and beta-MgH2 were performed to investigate the influence of Al and Si as impurities and the presence of high pressure phases on the properties of hydrogen sorption of magnesium hydride. The ab initio plane wave pseudopotential method based on density functional theory within the generalized gradient approximation was used in the present study. The total energies of the considered systems were calculated as a function of cell volume to obtain material properties such as bulk modulus K-0, equilibrium cell volume V-0 and minimum energy E-0(V-0). From the density of states (DOS) analysis, it was shown that doping MgH2 with Al and Si caused a reduction in the band gaps of each of the three phases. The diminished band gaps made the Mg-H bond more susceptible to dissociation. The destabilization of the hydrides was reflected in the decreased heats of formation of the doped hydrides, with the following Delta H-f order: Si < Al and beta < gamma < alpha. A 30.5% reduction in the activation energy barrier E-act for H-2 desorption was calculated for the Al-doped alpha-MgH2(001) surface and a 15.5% decrease in E-act of the Si-doped gamma-MgH2(001) surface was deduced, while doping with Al and Si increased the activation energy barrier for the beta-MgH2 (001) surface drastically.